IDENTIFIKASI TINGKAT PEMAHAMAN PESERTA DIDIK KELAS XI TERHADAP CYBERBULLYING FLAMING DI MAN 1 MUARO JAMBI - Retno Anastasya Bahri; Ninil Elfira; Muhammad Zulfikar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
As technology continues to grow, the internet and social media are increasingly used for communication and self-expression, especially among teenagers. However, this ease of access also leads to misuse, including cyberbullying. This study aims to explain how well 11th-grade students at MAN 1 Muaro Jambi understand flaming as a form of cyberbullying. Using a quantitative descriptive method and Simple Random Sampling, 36 students were selected as respondents. Data were obtained through a questionnaire and analyzed using frequency and percentage. The results show different levels of understanding: rude language (8%), openly expressing anger (15.22%), using capital letters or symbols to show emotion (20.35%), and verbally attacking others (11.69%). Overall, students’ understanding of flaming as cyberbullying is considered fairly good.